Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan U Neulheu Pada Gampong Paya Bujok Seuleumak, Kota Langsa - Suci Fadila; Muhazir Muhazir; Nanda Herijal Putra (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2025)
Micro, small, and medium enterprises (UMKM) play a vital role in driving local economic growth. However, many UMKM face limitations in marketing and business development, as seen in the case of the roasted coconut business owned by Mr. Ishak and Mrs. Nasriah in Gampong Paya Bujok Seuleumak, Langsa City. This business has been operating for six years, utilizing coconuts sourced from local residents to produce roasted coconut, with a daily production capacity of approximately 300 coconuts. The product is marketed based on customer orders to several regions, such as Peunaron, Peureulak, and Lokop, at a price of around IDR 35,000 per kilogram. This community engagement activity aimed to identify the potential and challenges faced by the roasted coconut MSME and to formulate strategies for broader marketing development. The method used was Participatory Action Research (PAR), in which students from the State Islamic Institute (IAIN) Langsa, while conducting community service (KKN), actively participated in the production process and engaged in participatory discussions with the business owners. The results showed that the roasted coconut business has significant potential to grow in terms of both product quality and market reach. However, limited marketing strategies and digital access remain key challenges. Therefore, continued assistance is recommended in areas such as packaging, branding, and the use of social media as a promotional tool. These efforts are expected to expand the market reach of roasted coconut products beyond the East Aceh region.